Flowering-time plasticity facilitates niche shifts in adjacent populations - Levin, Donald A. (The New phytologist, 2009)
The potential for a habitat shift is enhanced when selection against immigrants is augmented by a temporal difference between them and inhabitants of core populations. Genetically mediated changes in flowering time often accompany niche shifts in plants. The possibility that temporal change may arise from plastic responses to novel, stressful, environments rather than from genetic alteration has not been explored. This option is considered here, and it may be quite common. The substantial literature on transplant and common garden experiments shows that invaders of novel habitats are likely to undergo a developmentally based phenological shift. A phenological change in the invading population leads to assortative mating within populations, which in turn facilitates the evolution of local adaptation by the invader. Environmental induction may be the sole contributor to temporal change, or this factor may act in concert with genetic change. Flowering shifts based on developmental responses are immediate, not subject to remediation by gene flow and not affected by a paucity of genetic variation, negative genetic correlations or antagonistic pleiotropy, all of which might constrain phenological evolution.